The antimalarial activities of methylene blue and the 1,4-naphthoquinone 3-[4-(trifluoromethyl)benzyl]-menadione are not due to inhibition of the mitochondrial electron transport chain - Ehrhardt, Katharina; Davioud-Charvet, Elisabeth; Ke, Hangjun; Vaidya, Akhil B.; Lanzer, Michael; Deponte, Marcel (Antimicrobial agents and chemotherapy, 2013)
Methylene blue and a series of recently developed 1,4-naphthoquinones, including 3-[4-(substituted)benzyl]-menadiones, are potent antimalarial agents in vitro and in vivo. The activity of these structurally diverse compounds against the human malaria parasite Plasmodium falciparum might involve their peculiar redox properties. According to the current theory, redox-active methylene blue and 3-[4-(trifluoromethyl)benzyl]-menadione are “subversive substrates.” These agents are thought to shuttle electrons from reduced flavoproteins to acceptors such as hemoglobin-associated or free Fe(III)-protoporphyrin IX. The reduction of Fe(III)-protoporphyrin IX could subsequently prevent essential hemoglobin digestion and heme detoxification in the parasite. Alternatively, owing to their structures and redox properties, methylene blue and 1,4-naphthoquinones might also affect the mitochondrial electron transport chain. Here, we tested the latter hypothesis using an established system of transgenic P. falciparum cell lines and the antimalarial agents atovaquone and chloroquine as controls. In contrast to atovaquone, methylene blue and 3-[4-(trifluoromethyl)benzyl]-menadione do not inhibit the mitochondrial electron transport chain. A systematic comparison of the morphologies of drug-treated parasites furthermore suggests that the three drugs do not share a mechanism of action. Our findings support the idea that methylene blue and 3-[4-(trifluoromethyl)benzyl]-menadione exert their antimalarial activity as redox-active subversive substrates.
Gesehen am 08.01.2021